2013
DOI: 10.1002/ppap.201200114
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach for Direct Decomposition of Nitrous Oxide Assisted by Non‐Thermal Plasma

Abstract: Direct decomposition of nitrous oxide (N2O) was studied in a non‐thermal plasma (NTP) dielectric barrier discharge (DBD) reactor operated under ambient conditions. Influence of various parameters like discharge gap, input power, residence time, and N2O concentration were studied to achieve high conversions. The conversion decreased with increasing flow rate and N2O concentration. Typical results indicated that N2O decomposition may be efficient at high residence time and low concentrations. The degree of N2O d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Inserting observation on metal oxides integration to plasma is the increased selectivity towards total oxidation (CO 2 ) for the range of CB concentration studied. This increase is significant when SMF modified with MnO x , which may be due to the formation of a strong oxidizing agent, atomic oxygen by in situ decomposition of ozone . A similar observation was made at 530 J L −1 (Figure S1, Supporting Information) that confirmed the fact that increasing concentration decreases the conversion.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Inserting observation on metal oxides integration to plasma is the increased selectivity towards total oxidation (CO 2 ) for the range of CB concentration studied. This increase is significant when SMF modified with MnO x , which may be due to the formation of a strong oxidizing agent, atomic oxygen by in situ decomposition of ozone . A similar observation was made at 530 J L −1 (Figure S1, Supporting Information) that confirmed the fact that increasing concentration decreases the conversion.…”
Section: Resultssupporting
confidence: 75%
“…During the recent years, non‐thermal plasma (NTP) assisted removal of contaminants has been receiving great attention due to the specific advantageous like short reaction duration, ambient reaction conditions, etc. During the NTP treatment, majority of the supplied energy will be utilized for creating energetic electrons and almost no energy is wasted in heating the flue gas . However, NTP is non‐selective and may lead to the formation of undesired by‐products such as CO, CO 2 , and NO x .In order to overcome these limitations, catalytic plasma approach has been proposed …”
Section: Introductionmentioning
confidence: 99%
“…Dielectric barrier discharges (DBDs) at atmospheric pressure [1][2][3][4] usually occur in the filamentary regime in most gases [5]. These filaments are developed by electron avalanches at high voltage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Non‐thermal plasma (NTP) in aqueous media is considered to be one of the advanced oxidation process; where discharges at gas–liquid interface may produce strong oxidants like hydroxyl radical that are capable of mineralizing the pollutant. It has been reported that NTP operated in dielectric barrier discharge (DBD) configuration may produce UV radiation, shock waves, ions (H + , H 3 O + , O + , H − , O − , OH − , O 2 − ), molecular species (H 2 , O 3 , H 2 O 2 ), and most importantly reactive radicals (such as O • , H • ,OH • ) . Hydroxyl radicals produced at air–water interface may also produce hydrogen peroxide .…”
Section: Introductionmentioning
confidence: 99%